Advanced macroeconomics - Romer, David (Boston : McGraw-Hill, 2001)
A standard text and the starting point for graduate macro courses and helps lay the groundwork for students to begin doing research in macroeconomics and monetary economics.
Includes bibliographical references (p. 588-625) and index.
oif 28/04/15
Loan
Keywords: Macroeconomics